Efficiency of mathematical education in Poland - Biernacki, Marek; Czesak-Woytala, Katarzyna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
Based on the analysis of international exam results, which was carried out with OECD-PISA in mathematics among Polish students of gimnazjum (secondary school) in 2003-2009, and based on the results of the exam in mathematics among students of the first year in the University of Economics in Wroclaw in 2009-2012; the article shows that Polish education in mathematics is, unfortunately. Currently at the level typical for a communist system, i.e. one which is not developing the ability to solve new or sophisticated problems and not practicing new methods for these problems, and as a result, is not open to the needs of a market economy.
Didactics of Mathematics, 2012, Nr 9 (13), s. 5-14
Keywords: effectiveness of mathematics education; PISA; Programme for International Student Assessment